Changes of China's agri-food exports to Germany caused by its accession to WTO and the 2008 financial crisis. Issue 2 (5th May 2015) - Guo, Zhichao; Feng, Yuanhua; Gries, Thomas
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate changes of China's agri-food exports to Germany caused by China's accession to WTO and the global financial crisis in a quantitative way. The paper aims to detect structural breaks and compare differences before and after the change points. Design/methodology/approach – The structural breaks detection procedures in this paper can be applied to find out two different types of change points, i.e. in the middle and at the end of one time series. Then time series and regression models are used to compare differences of trade relationship before and after the detected change points. The methods can be employed in any economic series and work well in practice. Findings – The results indicate that structural breaks in 2002 and 2009 are caused by China's accession to WTO and the financial crisis. Time series and regression models show that the development of China's exports to Germany in agri-food products has different features in different sub-periods. Before 1999, there is no significant relationship between China's exports to Germany and Germany's imports from the world. Between 2002 and 2008 the former depends on the latter very strongly, and China's exports to Germany developed quickly and stably. It decreased, however suddenly in 2009, caused by the great reduction of Germany's imports from the world in that year. But China's market share in Germany still had a small gain. Analysis of two categories in agri-food trade also leads to similar conclusions. Comparing the two events we see rather different patterns even if they both indicate structural breaks in the development of China's agri-food exports to Germany. Originality/value – This paper partly originally proposes two statistical algorithms for detecting different kinds of structural breaks in the middle part and at the end of a short-time series, respectively.